Association between e-cigarette use and susceptibility to tobacco product use: findings from the 2019 China National Youth Tobacco Survey - Sixuan Li; Sixuan Li; Xinying Zeng; Xinbo Di; Shiwei Liu (Frontiers Media S.A., 2024)
BackgroundThere is an ongoing debate about whether e-cigarettes act as a gateway to tobacco smoking or contribute to smoking cessation, and relevant studies are limited among Chinese adolescents. This cross-sectional study therefore aimed to explore the relationship between e-cigarette use and susceptibility to tobacco product use among Chinese high school students.MethodsThe study population comprised 107,633 never smokers and 19,377 former smokers, generated from the 2019 China National Youth Tobacco Survey. The primary independent variables of interest were ever e-cigarette use, current e-cigarette use, and the frequency of current e-cigarette use. The main outcome was the susceptibility to tobacco product use. Multilevel logistic regression was used to estimate the association between the primary independent variables of interest and the outcome variable. Moreover, two additional multilevel logistic regression models were fitted using two alternative definitions of the outcome as the sensitivity analyses.ResultsAmong never smokers, students who ever used e-cigarettes were more likely to be susceptible to tobacco product use compared to students who never used e-cigarettes (AOR = 2.83, 95%CI = 2.59-3.08). Students who currently used e-cigarettes were more likely to be susceptible to tobacco product use than those who did not currently use e-cigarettes (AOR = 3.89, 95%CI = 3.21-4.72). Among former smokers, with the same settings of modeling, the AORs were 1.76 (95%CI = 1.62-1.91) and 3.16 (95%CI = 2.52-3.97), respectively. Similar results were obtained from the two sensitivity analyses.ConclusionAmong Chinese high school students, both never smokers and former smokers, e-cigarette use, especially current e-cigarette use, was positively associated with susceptibility to tobacco product use. It is recommended to strengthen the monitoring of e-cigarettes and to provide targeted health education to adolescents.